I, You and The Others, Among Otherness, Diversity and Education - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2023)
When you think of the other and the other, they are not due to the same power and hegemonies, and that this other is identified as a face, there is the possibility of guiding behavior or ethics, along the paths of diversity, understood It is like the discovery of diversity and otherness in education, which are the most appropriate ways to understand that the autonomous self, is in debt, under the figure of hostage. Humanity has begun a path which has no possible reserve and this consists in opening, via postmodernity, a type of thought that is capable of generating scenarios of recognition of what is different, as a discovery that benefits everyone and everyone greatly. To propose that otherness is the basis on which diversity is built, is now an open route in education and to travel that makes life more meaningful because of the ethical recognition of the other and the other that will accompany me on a path of history.